Integrative Analysis of miRNA and mRNA Expression Profiles Associated With Human Atrial Aging - Yao, Yan; Jiang, Chenxi; Wang, Fan; Yan, Han; Long, Deyong; Zhao, Jinghua; Wang, Jiangang; Zhang, Chunxiao; Li, Yang; Tian, Xiaoli; Wang, Qing K.; Wu, Gang; et al. (Frontiers in Physiology, 2019)
Background Limited findings have been reported to systematically study miRNA and mRNA expression profiles in aged human atria. In this study, we aimed to identify miRNAs, genes, and miRNA-mRNA interaction networks for human atrial aging (AA). Methods Right atrial appendages from twelve patients who received aortic valve replacement were subjected to miRNA-seq and RNA-seq. All the patients were in sinus rhythm (SR) and stratified by age into four groups. Differential expression analysis was carried out to identify miRNAs and genes for human AA. The miRNA-mRNA interactions for human AA were identified by Pearson correlation analysis and miRNA target prediction programs. Results Seven miRNAs (4 upregulation and 3 downregulation) and 42 genes (23 upregulation and 19 downregulation) were differentially expressed in human right atrial tissues between older samples and younger samples. Bioinformatic analysis identified 114 pairs of putative miRNA-mRNA interactions on AA and four types of correlation. Pathway enrichment analysis identified over 40 significant pathways and the top three pathways included rhythmic process (P=7.5x10-5, Q=0.034), senescence and autophagy in cancer (P=9.0x10-5, Q=0.034), and positive regulation of cytokine biosynthetic process (P=1.1x10-4, Q=0.034). Conclusions Our study revealed novel miRNA-mRNA interaction networks and signaling pathways for AA, providing novel insights into the development of human AA. Future studies are needed to investigate the potential significance of these miRNA-mRNA interactions in human AA or AA-related cardiovascular diseases.